2015
DOI: 10.1021/acscatal.5b01918
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of N2 to Ammonia at Ambient Conditions on Mononitrides of Zr, Nb, Cr, and V: A DFT Guide for Experiments

Abstract: A rapid and facile reduction of nitrogen to achieve sustainable and energy-efficient production of ammonia is critical to its use as a hydrogen storage medium, chemical feedstock, and especially for manufacturing inorganic fertilizers. For a decentralization of catalytic ammonia production, small-scale N2 reduction devices are required that are equipped with the most stable, selective, and active catalysts that operate at low temperature and ambient pressure. Here, we report the development of new and cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
313
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(352 citation statements)
references
References 51 publications
15
313
1
3
Order By: Relevance
“…56 NbN and CrN may also act in a similar fashion. 57 As yet, it would again seem that no such nitride materials have been tested experimentally as cathodes for nitrogen electroreduction, and so it would be very interesting to see if they performed as anticipated in real-world situations. It would also be very useful if the same kind of theoretical investigations that have been performed on these simple nitrides could be extended to binary nitrides.…”
Section: Recent Theoretical Insights Into Electrocatalytic Nitrogen Rmentioning
confidence: 99%
“…56 NbN and CrN may also act in a similar fashion. 57 As yet, it would again seem that no such nitride materials have been tested experimentally as cathodes for nitrogen electroreduction, and so it would be very interesting to see if they performed as anticipated in real-world situations. It would also be very useful if the same kind of theoretical investigations that have been performed on these simple nitrides could be extended to binary nitrides.…”
Section: Recent Theoretical Insights Into Electrocatalytic Nitrogen Rmentioning
confidence: 99%
“…The single N-vacancy approach studied for the (100) facets [4,14] is not applicable here due to the closely packed structure of the (111) surfaces where N atoms are protruded from the surface. Hydrogenation of the surface is carried out by adding H atoms one-by-one to the surface to represent a proton from the solution and an electron from the electrode.…”
Section: Reaction Pathways and Electrochemical Modelingmentioning
confidence: 99%
“…In many cases, N 2 adsorption to the N-vacant site(s) becomes an exothermic process on TMNs [4] compared to when N 2 needs to be adsorbed on pure transition metals [9,12] or on clean TMNs [13], which is usually endothermic. Therefore, it is interesting to investigate catalytic reactions like nitrogen activation on these TMN surfaces via a MvK mechanism where its feasibility has recently been reported on different TMNs [3,4,10,14]. All these characteristics mentioned above, together with high resistance against corrosion and high http://dx.doi.org/10.1016/j.cattod.2016.06.009 0920-5861/© 2016 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we found that N 2 can be activated at a surface cavity where N 2 is bound side-on a Co 8 cluster at the 16e Wyckoff site or it can be activated at surface 3f-nitrogen vacancies where N 2 is activated in an end-on configuration [12]. There are other DFT studies that have shown that N-vacancies can participate in the mechanism for ammonia synthesis, such as in the electrochemical reduction of ammonia on Zr, Nb, Cr, V mononitrides [14][15][16] and in the two-phase solarenergy driven ammonia synthesis on metal-nitrides [17,18]. End-on activated N 2 also exists in Fe(0) complexes (i.e.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%